Thinking While Walking: Experienced High-Heel Walkers Flexibly Adjust Their Gait - Schaefer, Sabine; Lindenberger, Ulman (Frontiers in Psychology, 2013)
Theories of motor skill acquisition postulate that attentional demands of motor execution decrease with practice. Hence, motor experts should experience less attentional resource conflict when performing a motor task in their domain of expertise concurrently with a demanding cognitive task. We assessed cognitive and motor performance in high-heel experts and novices who were performing a working memory task while walking in gym shoes or high heels on a treadmill. Surprisingly, neither group showed lower working memory performance when walking than when sitting, irrespective of shoe type. However, high-heel experts adapted walking regularity more flexibly to shoe type and cognitive load than novices, by reducing the variability of time spent in the single-support phase of the gait cycle in high heels when cognitively challenged. We conclude that high-heel expertise is associated with more flexible adjustments of movement patterns. Future research should investigate whether a more demanding walking task (e.g., wearing high heels on uneven surfaces and during gait perturbations) results in expertise-related differences in the simultaneous execution of a cognitive task.